PENGARUH KUALITAS PRODUK, HARGA DAN LOKASI TERHADAP MINAT BELI ULANG(Studi Pada Konsumen Kopi Nako Summarecon Bekasi) - Munawar, Fatah Al; Supriyanto, Supriyanto; Wijayanti, Murti; Siahaan, Matdio (SINERGI : Jurnal Riset Ilmiah, 2025)
The Influence of Product Quality, Price, and Location on Repurchase Intention (A Study on Consumers of Kopi Nako Summarecon Bekasi). This study aims to examine the influence of product quality, price, and location on repurchase intention among consumers of Kopi Nako Summarecon Bekasi. The background of this research is based on the increasingly intense competition in the coffee shop industry, which requires business owners to continuously improve product quality, determine appropriate pricing, and choose strategic locations in order to maintain customer loyalty. This research employs a quantitative method with a descriptive approach. Data were collected through questionnaires distributed to 126 respondents who had previously made purchases at Kopi Nako Summarecon Bekasi. Data analysis was carried out using multiple linear regression with the Statistical Product and Service Solutions (SPSS) software version 26. The results show that product quality, price, and location have a positive and significant influence on repurchase intention. Simultaneously, these three variables also have a significant and positive effect on repurchase intention. This study is expected to serve as a reference for coffee shop business owners in designing more targeted marketing strategies to enhance customer loyalty